Embedded scheme of work structure into learning management system - Nik Nurul Hafzan, Mat Yaacob (2016)
This research is related to the automatic integration of the Teaching Plan (TP) or Scheme of Work (SOW) into Moodle; a popular course management software (CMS). SOW is a document prepared by academic teachers to detail out a plan of the course throughout the teaching duration. It helps to better manage student activities such as quizzes, exam, topics, and etc. However, most departments like the School of Computing (SOC) normally prepare the document manually. Moodle allows for course to be managed effectively though the use of a web service. There are hundreds of features provided by Moodle to assist in teaching. Moodle divides the teaching duration according to pre-set dates. Current Moodle practice is that the SOW needs to be added manually into the SOW section of Moodle. This study found that most of the time, the lecturers’ SOW documents are not the same with their Moodle content and thus would have to modify accordingly. This is due to the manual entry for the SOW in the Moodle system that takes time and becomes cumbersome. This study presents a potential solution and describe show the SOW structure can be integrated automatically according to the weekly activities, like assignments and quizzes, by using a plugin developed in this study. The methodology used in this study is made up of five steps, namely, the awareness of the problem, suggestion, development, evaluation, and conclusion. Based on the evaluation performed through sampling, the plugin developed through this study has significant value by saving precious time in assisting the academician’s task of updating and using Moodle, specifically related to the SOW.